Respon Pertumbuhan dan Hasil Kedelai dengan Aplikasi Pupuk Organik dan Rhizobium - Nadia Fransiska; Tri A Lestari; Ratna Santi (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2023)
Soybean are basic need and the main source of vegetable protein for most of the Indonesian population. Organic matter and Rhizobium are improvement efforts to optimize soybean growth between durian plants. The purpose of the research was to determine the use of Rhizobium and organic fertilizers on the growth and yield of soybeans between durian plants in LubukKelik village, Bangka. The experiment used split plot and RAL design. The main plot was Rhizobium applications consist of without Rhizobium (P0) and Rhizobium application (P1). The sub plot was the use of organic fertilizers, which consists of chicken manure (K1) and empty oil palm fruit bunches compost (K2). The results showed that the types of organic fertilizer application not significantly affected soybeans growth dan yield in between durian plants. Empty fruit bunches compost provided the best growth on soybean plants. The best yield of soybean in between durian plants are shown by empty fruit bunches treatment. Rhizobium application significantly affected growth parameters of soybean and effective root nodules. Soybean growth parameters with Rhizobium application was better than without Rhizobium application. Interaction between organic fertilizers and Rhizobium significantly not affected soybeans growth dan yield. Combination of empty oil palm fruit bunches compost with Rhizobium is treatments that provide the best growth of soybean.